Intrinsic structural-ballistic interactions in composite energetic materials. Part I – Experiments - G. Sandri Tussiwand; F. Maggi; Bandera, A.; L. T. De Luca (ՀՀ ԳԱԱ հրատ.)
Among the various aspects of the deflagration of composite solid rocket propellants, one deserving further attention is the dependence of the propellant regression rate on its mechanical state, properties and applied loads during deflagration. Beside structural-ballistic interaction phenomena occurring on a motor level, i.e. affecting the whole grain or large portions of it, the structural properties of a propellant and the mechanical loads acting during deflagration can significantly alter its combustion behavior on a microscopic scale, leading to what can be considered as an “intrinsic” coupling mechanism.
Keywords: Քիմիա